Examination of Da'wah Communications on the Instagram @fuadhnaim Utilising Roland Barthes' Semiotic Framework - Ramadhani, Suci; Siregar, Amran Pikal; Sitorus, Ari Oldwin; Ginting, Abdul Fikri; Sikumbang, Ahmad Tamrin (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
This study examines the application of Roland Barthes' semiotic theory in the analysis of da'wah messages disseminated through the social media platform Instagram. This research involved analyzing content posted by the @fuadhnaim account from January to October 2024. The research seeks to elucidate the denotative, connotative, and mythological significances embedded in reel-shaped preaching messages, while also examining the utilization of visual and verbal symbols to communicate Islamic ideals in the digital age. The employed methodology is descriptive qualitative, utilizing content analysis as the primary data collection tool. An investigation of the @fuadhnaim Instagram account revealed that the da'wah messages comprised five postings on faith, four on sharia, four pertaining to worship, and nine about morals. Certain reels also address prevalent topics and offline research articles. The da'wah themes presented encompass self-reflection, prayer, and critique of promiscuity, alongside an examination of falsehoods that expose social constructs, like the morality of